Reliability and validity of the Cystic Fibrosis Questionnaire-Revised for children and parents in Turkey: cross-sectional study - KARADAĞ, BÜLENT TANER (SPRINGER, 2013)
The purpose of study was to translate Cystic Fibrosis Questionnaire-Revised (CFQ-R) into Turkish for children with cystic fibrosis (CF) and evaluate its reliability and validity. This is the first CF-specific health-related quality of life (HRQOL) measure validated in a Muslim country. Fifty-one children aged 6-13 years treated at four centers in Turkey and 30 parents participated in this cross-sectional study. Demographic characteristics and disease severity parameters were recorded for all participants. All participants completed the parent or child versions of CFQ-R and KINDL questionnaires at enrollment. Reliability and construct validity analysis were carried out. Both children and parents endorsed a range of responses, with no evidence of floor or ceiling effects. Item-to-total correlations indicated that most items were more highly correlated with their intended scale than competing scales. Good internal consistency was found for majority of child and parent scales. CFQ-R scales correlated significantly with clinical indices of disease severity. Good evidence of convergent validity with a generic HRQOL scale was found. Turkish versions of CFQ-R Child and Parent instruments have demonstrated adequate reliability and validity and can be utilized in clinical trials or integrated into clinical evaluation and follow-up of Turkish children with CF.
Keywords: Cystic Fibrosis Questionnaire-Revised; Cystic fibrosis; Validity; Reliability; QUALITY-OF-LIFE; INHALED AZTREONAM LYSINE; PSYCHOMETRIC PROPERTIES; AIRWAY PSEUDOMONAS; VALIDATION; ADOLESCENTS; ADULTS; SATISFACTION